Tourism as a Standalone Discipline in Indonesia: A Decade of Evidence from Tourism Village Research - Rahman, A. Faidlal; Wiweka, Kadek; Sandi Wachyuni , Suci; Pramania Adnyana, Putu; Lochan, Amarjiva (Graduate School, Universitas Brawijaya, 2026)
This study reviews a decade of academic publications on rural tourism and tourist villages in Indonesia to clarify the development of the field and examine how both concepts are approached in national scholarship. The review pursues two objectives: assessing the progress of academic research between 2009 and 2019, and analysing the substantive characteristics of published articles in terms of scope, methodology, and thematic discussion. Despite the increasing volume of publications, previous studies have not systematically mapped the intellectual structure, thematic concentration, and methodological patterns of rural tourism and tourist village research at the national level, resulting in a clear research gap in understanding the consolidation of tourism as an academic discipline in Indonesia. A mixed-methods design was employed using a netnographic approach supported by text mining, network analysis, and content analysis. The research corpus was drawn from 46 Indonesian tourism journals, comprising 2,249 articles, from which keyword filtering identified 333 relevant publications (107 on tourist villages and 226 on rural tourism). Data processing and visualisation utilised AntConc, RStudio, and Gephi. The findings reveal that the growth of research in both domains has been strongly influenced by government intervention through the Ministry of Education and the Ministry of Tourism. The analysis also indicates that tourist villages and rural tourism are treated as conceptually similar within Indonesian academic discourse. Three key recommendations emerge: the need to broaden thematic perspectives, diversify methodological approaches, and strengthen the depth of scholarly discussion. Theoretically, this study contributes to tourism studies by positioning rural tourism and tourist village research as an empirical foundation for recognising tourism as a standalone academic discipline, particularly through the integration of policy-driven knowledge production, methodological pluralism, and interdisciplinary inquiry. Overall, this study offers a national-scale overview of research development and provides a foundation for future rural-based tourism research in Indonesia.